Christine Montalbetti's Unreasonable Mission. Issue 4 (2nd October 2021) - Motte, Warren
Abstract: In Mon ancêtre Poisson (2019), Christine Montalbetti looks through her family tree in order to find the oldest ancestor whom she can identify, one Jules Poisson (1833–1919), her great-great-grandfather. The book is quite unlike any other that she has written to this point, and it bears the traces of a variety of techniques. A great deal of documentary, archival research certainly went into it, but so did a lot of speculation. Hard fact and objective, even scientific data rub elbows with very personal considerations. Flatly declarative narration gives way to an impassioned intergenerational conversation, and vice versa. Montalbetti's project is not merely biographical in character. It is a novel, after all, and if its main protagonist often occupies the center of the narrative stage, the book is not solely and uniquely about him. For if Montalbetti is manifestly concerned with understanding who her great-great-grandfather was in his life, she is also concerned with what that very understanding might mean in her own life. In other terms, this is a book about him, but it is also a book about her—and about the vexed notion of contact between one person and another, across a gap measuring several generations.